PILIHAN KARIR SEBAGAI KONSULTAN PAJAK DENGAN PELATIHAN BREVET PAJAK VARIABEL MODERATING - Sugeng; Prasetyo, Eko (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
Abstract The purpose of this study is to analyze career selection as a tax consultant. The independent variable used is perception and motivation, with the variable interest in participating in tax brevet training. The sample used in this study is accounting students in Kediri, who have gone through taxation courses, using the Slovin formula obtained a sample of 84 students. The analysis technique used in this study is Partial Least Square (PLS). From the results of direct testing, the results show that tax brevet perceptions and training affect career choice as a tax consultant, but motivation does not directly affect career selection as a tax consultant. The test results do not directly get the results that perceptions and motivations influence career choice as a tax consultant with interest in participating in tax brevets as a moderating variable.